2022
DOI: 10.1002/jcp.30817
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy blockade potentiates cancer‐associated immunosuppression through programmed death ligand‐1 upregulation in bladder cancer

Abstract: A high basal level of autophagic flux in bladder cancer (BC) cells prevents cell death and weakens chemotherapy efficacy. However, how autophagy influences cancerassociated immunosuppression in BC remains undetermined. In this study, we observed a negative correlation between the autophagy-related markers LC3-II and programmed death ligand-1 (PD-L1) in BC cells. The autophagy inhibitors chloroquine (CQ) and bafilomycin A1 (Baf-A1) increased PD-L1 expression in BC cells through the ERK-JNK-c-Jun signal-transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Similarly, combined RT, mTOR and PD-1 inhibitors could enhance radiosensitivity in cervical cancer by promoting autophagy [174]. Consistently, Tsai et al indicated that autophagy blockade by inhibitors increased PD-L1 expression through the ERK and JNK signaling pathways in bladder cancer cells [175]. In contrast, other studies have shown that PD-L1 can inhibit autophagy by activating mTORC1 signaling and inhibiting mTORC2 signaling [176].…”
Section: The Dual Roles Of Autophagy In Rt Immunotherapy and Nanotech...mentioning
confidence: 88%
“…Similarly, combined RT, mTOR and PD-1 inhibitors could enhance radiosensitivity in cervical cancer by promoting autophagy [174]. Consistently, Tsai et al indicated that autophagy blockade by inhibitors increased PD-L1 expression through the ERK and JNK signaling pathways in bladder cancer cells [175]. In contrast, other studies have shown that PD-L1 can inhibit autophagy by activating mTORC1 signaling and inhibiting mTORC2 signaling [176].…”
Section: The Dual Roles Of Autophagy In Rt Immunotherapy and Nanotech...mentioning
confidence: 88%
“…Previous study has demonstrated that the expression levels of PD-L1 negatively associates with autophagic activities, and autophagy inhibition increases PD‐L1 expression leading to immune evasion in bladder cancer (Tsai et al. 2022 ). Additionally, autophagy-related genes signature has been proved to be efficient in predicting immunotherapeutic effect in bladder cancer (Cao et al.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-34a also negative regulates EMT activity by targeting EMT-transcription factors ZEB1 (41), Snail (42) and Twist (43) in various cancers, showing the broad potency of miR-34a as a tumor suppressor. Moreover, miR-34a has been reported to be involved in tumor-mediated immunosuppression (44,45). Mechanistically, the overexpression of miR-34a in cells from acute myeloid leukemia blocks PD-L1 surface expression, which interrupts PD-L1-specific T cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%